Dosage Determination of Galangal Extract (Alpinia purpurata) Through LC50-96 Method on Zebrafish Larvae (Danio rerio) as a Model - Amanullah, Muhammad Azmi; Widodo, Maheno Sri; Faqih, Abdul Raheem (Journal of Applied Science, Engineering, Technology, and Education, 2022)
Galangal (Alpinia purpurata) is a herb and medicine plant that is found in Southeast Asia including Thailand, Malaysia, and Indonesia. It is known to have health benefits for its flavonoid, phytosterol, and phenols that are anti-oxidant, anti-cancer, and anti-fungal properties. The phytosterol also can be used for sex hormones production.The exploration of its uses in aquaculture are not yet fully understand. In this LC50-96 experiments were tested for its optimum dosage used in aquaculture by using zebrafish larvae (Danio rerio) as a model. The optimum dosage in the experiments were between 1—31,83 ppm for ethanolic extract of galangal and <0,83 ppm for methanolic extract of galangal. Its uses in aquaculture must be further explored by its effect in fishes behaviors or by the histology of the organs.